THE PERSPECTIVE OF ISLAMIC PHILOSOPHY, SUFISM, ISLAMIC JURISPRUDENCE AND JAVANESE TRADITION ON WOMEN - Soleh, Achmad Khudori; Rahmawati, Erik Sabti; Camila, Humaida Ghevira Syavia; Buang, Ahmad Hidayat (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Islamic philosophy, Sufism, Islamic jurisprudence, and Javanese traditions offer diverse and sometimes conflicting perspectives on the status and role of women. While some schools of thought position women as subordinate to men, others advocate for gender equality and even recognize female leadership over men. This study aims to analyze and compare these varied viewpoints through a qualitative literature review, drawing primarily from foundational texts and primary sources. The findings reveal that Islamic philosophy, as represented by al-Fârâbî (870–950), and Sufism, particularly in the works of Ibn Arabi (1165–1240), uphold a vision of gender equality, emphasizing the shared spiritual and intellectual capacities of women and men. In contrast, classical Islamic jurisprudence tends to place women in a subordinate position, often restricting their roles in public and legal spheres. The Javanese tradition presents a dualistic stance: while it recognizes women as integral to male identity and capable of leadership, it simultaneously perpetuates notions of women as possessions or appendages to men. This ambivalence reflects the syncretic nature of Javanese culture, shaped by both indigenous and Islamic influences. Given the persistent gender disparities in contemporary Muslim societies, this study argues for a greater dissemination and integration of the more egalitarian views found in Islamic philosophy and Sufism. Such perspectives offer theological and cultural resources for advancing a more balanced and respectful relationship between men and women. Ultimately, the study contributes to broader debates on gender, religion, and tradition in the Muslim world, advocating for a reevaluation of normative frameworks surrounding women.